Leveraging Triple Helix Synergy for Boosting SME Innovation and Competitiveness: Insights from Blitar - Suwigda Agung Novandinata; Siti Azizah; Dede Aprylasari (Agriwar Journal, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia play a vital role in the country's economy. Still, they face various challenges, including limited resources, low managerial capabilities, and a lack of access to modern technology. The triple helix approach, which involves academics, business actors, and the government, can be a solution to increase the innovation and competitiveness of MSMEs. This research examines the synergy of the triple helix in developing MSMEs, with a case study of the MSME "MUZA" in Blitar Regency, which produces smoked salted eggs as an innovative product from traditional products. The research method employed is a descriptive exploratory approach, collecting data through in-depth interviews and questionnaires. The research results indicate that, despite training and support from academics and the government, the involvement of MSMEs in implementing training still needs improvement. There are challenges in coordination between related parties which hinder the effectiveness of empowerment. This research highlights the importance of fostering further synergy among academics, the Government, and MSMEs to create an ecosystem that supports the development of more sustainable and competitive MSMEs in both domestic and international markets.